Jan Chryzostom o śpiewie i muzyce. Zarys problematyki - Szczur, Piotr (Vox Patrum, 2018)
This article has been divided into three parts. The first part discusses the importance of singing and music in Jewish and Christian traditions; the second part discusses Chrysostom’s observations on singing and secular music (a lot of space is devoted to criticizing the obscene songs) and Jewish; the last part of the article is devoted to Christian singing. John Chrysostom attributed the great importance of singing and music and pointed to their various positive functions and actions. However, he criticized apotropaic and convivial songs, and theatrical and wedding songs as well. He also spoke negatively about Jewish songs and music. Chrysostom encouraged to introduce the repertoire of Christian songs to every dimension of human existence. It had several goals: 1) to raise moral values of Christians’ life, who should avoid singing or listening to obscene theatrical songs; 2) to resist the strong influence of Judaism on a significant part of Christians in Antioch; 3) to establish the repertoire of Christian songs that would be sung for the glory of God.